Odpowiedzi

2009-12-17T18:12:42+01:00
A)(3x-1)²=9x²-2
9x²-6x+1=9x²-2
-6x=-3
x=¹/₂
b) 4x²=(5-2x)²
4x²=25-10x+4x²
0=25-10x
10x=25
x=2,5
Najlepsza Odpowiedź!
2009-12-17T18:16:14+01:00
A)
9x2-6x+1 = 9x2-2
9x2-9x2-6x = -1-2
-6x = -3
x = 1/2

b)
4x2 = (5-2x)2
4x2 = 25-20x+4x2
4x2-4x2+20x = 25
20x = 25
x = 25/20
x = 5/4
2009-12-17T18:17:25+01:00
A)
(3x-1)²=9x²-2
9x² - 6x +1 = 9x² -2
9x² -6x -9x² = -2 -1
-6x = -3
x = (-3) : (-6)
x = ½

b) 4x²=(5-2x)²
4x² = 25 - 20x +4x²
4x² +20x - 4x² = 25
20x = 25
x = 25/20
x = 5/4